Many-electron model for multiple ionization in atomic collisions - Archubi, Claudio Darío (2007)
We have developed a many-electron model for multiple ionization of heavy atoms bombarded by bare ions. It is based on the transport equation for an ion in an inhomogeneous electronic density. Ionization probabilities are obtained by employing the shell-to-shell local plasma approximation with the Levine and Louie dielectric function to take into account the binding energy of each shell. Post-collisional contributions due to Auger-like processes are taken into account by employing recent photoemission data. Results for single-toquadruple ionization of Ne, Ar, Kr and Xe by protons are presented showing a very good agreement with experimental data.